Detection of irradiation in talaba (Crassotrea iredalei), lukan (Cyrenna ventricosa) and paros (Psammotaea elongata) - Masiglat, Maria Bernadette V. (2004)
ABSTRACT Post-irradiation changes in thermal behavior and liquid behavior and liquid crystalline structures of the lipid components of talaba (Crassostrea iredalei), lukan (Cyrena ventricosa), and paros (Psammotaea elongata) through differential scanning calorimetry (DSC) and optical polarizing microscopy (OPM) were evaluated as markers of radiation treatment. DSC analysis showed that for talaba and paros, shifts in mean peak temperatures were observed for lower and higher temperatures, respectively. However, further verification is needed since one out of the three trials in irradiated talaba showed inconsistent mean peak temperature. For lukan, shifts in the two consistent mean peak temperatures for both non-irradiated and irradiated samples were observed. Different liquid crystalline structures were observed under the polarizing microscope for all samples. Non-irradiated talaba lipid revealed broken fan-like, batonnet, coarse mosaic, chiral-nematic structures, and positive and negative units. However, the irradiated lipid showed oily streaks and coarse mosaic structures only. From coarse mosiac, chiral-nematic, non-geometric textures, positive and negative units for non-irradiated lukan lipid, striations with different intense band of colors were observed in the irradiated lipid. For paros, non-irradiated lipids were mostly of the coarse mosaic, fan-like, and marbled textures while the irradiated lipids showed textures similar to those of the control including additional textures such as positive and negative units, oily streaks, batonnets and chiral-nematic. Results obtained revealed the feasibility of the combined use of DSC of lipids and OPM of liquid crystals as a rapid irradiation detection method in the three specimens.